Proceedings of the American Society for Enhanced Recovery/Evidence Based Peri-Operative Medicine 2016 Annual Congress of Enhanced Recovery and Perioperative Medicine. Issue 1 (September 2016) - Horres, Charles; Adam, Mohamed; Sun, Zhifei; Thacker, Julie; Miller, Timothy; Grant, Stuart; Huang, Jeffrey; McPherson, Kirstie; Patel, Sanjiv; Ng, Su; Veelo, Denise; Geerts, Bart; et al.
Table of contents A1 Effects of enhanced recovery pathways on renal function Charles R. Horres, Mohamed A. Adam, Zhifei Sun, Julie K. Thacker, Timothy J. Miller, Stuart A. Grant A2 Economic outcomes of enhanced recovery after surgery (ERAS) Jeffrey Huang A3 What does eating, drinking and mobilizing after enhanced recovery surgery really mean? Kirstie McPherson, Sanjiv Patel, Su Cheen Ng, Denise Veelo, Bart Geerts, Monty Mythen A4 Intra-operative fluid monitoring practices Su Cheen Ng, Mark Foulger, Tim Collins, Kirstie McPherson, Michael Mythen A5 Development of an integrated perioperative medicine care pathway Mark Edwards, Denny Levett, Tristan Chapman, Imogen Fecher – Jones, Julian Smith, John Knight, Michael Grocott A6 Cardiopulmonary exercise testing for collaborative decision making prior to major hepatobiliary surgery Mark Edwards, Thomas Sharp, Sandy Jack, Tom Armstrong, John Primrose, Michael Grocott, Denny Levett A7 Effect of an enhanced recovery program on length of stay for microvascular breast reconstruction patients Adam B. King, Kye Higdon, Melissa Bellomy, Sandy An, Paul St. Jacques, Jon Wanderer, Matthew McEvoy A8 Addressing readmissions associated with an enhanced recovery pathway for colorectal surgery Anne C. Fabrizio, Michael C. Grant, Deborah Hobson, Jonathan Efron, Susan Gearhart, Bashar Safar, Sandy Fang, Christopher Wu, Elizabeth Wick A9 The Manchester surgical outcomes project: prevalence of pre operative anaemia and peri operative red cell transfusion rates Leanne Darwin, John Moore A10 Preliminary results from a pilot study utilizing ears protocol in living donor nephrectomy Aparna Rege, Jayanth Reddy, William Irish, Ahmad Zaaroura, Elizabeth Flores Vera, Deepak Vikraman, Todd Brennan, Debra Sudan, Kadiyala Ravindra A11 Enhanced recovery after surgery: the role of the pathway coordinator Deborah Watson A12 Hospitalization costs for patients undergoing orthopedic surgery treated with intravenous acetaminophen (IV-APAP) + IV opioids or IV opioids alone for postoperative pain Manasee V. Shah, Brett A. Maiese, Michael T. Eaddy, Orsolya Lunacsek, An Pham, George J. Wan A13 Development of an app for quality improvement in enhanced recovery Kirstie McPherson, Thomas Keen, Monty Mythen A14 A clinical rotation in enhanced recovery pathways and evidence based perioperative medicine for medical students Alexander B Stone, Christopher L. Wu, Elizabeth C. Wick A15 Enhanced recovery after surgery (ERAS) implementation in abdominal based free flap breast reconstruction Rachel A. Anolik, Adam Glener, Thomas J. Hopkins, Scott T. Hollenbeck, Julie K. Marosky Thacker A16 How the implementation of an enhanced recovery after surgery (ERAS) protocol can improve outcomes for patients undergoing cystectomy Tracey Hong, Andrea Bisaillon, Peter Black, Alan So, Associate Professor, Kelly Mayson A17 Use of an app to improve patient engagement with enhanced recovery pathways Kirstie McPherson, Thomas Keen, Monty Mythen A18 Effect of an enhanced recovery after surgery pathway for living donor nephrectomy patients Adam B. King, Rachel Forbes, Brad Koss, Tracy McGrane, Warren S. Sandberg, Jonathan Wanderer, Matthew McEvoy A19 Introduction and implementation of an enhanced recovery program to a general surgery practice in a community hospital Patrick Shanahan, John Rohan, Desirée Chappell, Carrie Chesher A20 "Get fit" for surgery: benefits of a prehabilitation clinic for an enhanced recovery program for colorectal surgical patients Susan VanderBeek, Rebekah Kelly A21 Evaluation of gastrointestinal complications following radical cystectomy using enhanced recovery protocol Siamak Daneshmand, Soroush T. Bazargani, Hamed Ahmadi, Gus Miranda, Jie Cai, Anne K. Schuckman, Hooman Djaladat A22 Impact of a novel diabetic management protocol for carbohydrate loaded patients within an orthopedic ERAS protocol Volz L, Milby J A23 Institution of a patient blood management program to decrease blood transfusions in elective knee and hip arthroplasty Opeyemi Popoola, Tanisha Reid, Luciana Mullan, Mehrdad Rafizadeh, Richard Pitera